Irradiation Effects of 40 – 250 keV Fe ions on Structural and Optical Properties of CR-39 Polymer. (2015) - Butt, M.Z.; Ali, Dilawar; Najm-ul-Aarifeen,; Naseem, S.
Abstract: A passive Q-switched Nd:YAG pulsed laser was used to irradiate 99.99% pure Fe target in vacuum ∼10 -3 Torr. The CR-39 specimens were exposed to laser produced plasma ions (40-250 keV) emitted along the normal to the Fe target surface. The flux of Fe ions was varied by varying the number of laser shots in the range 500-1500 with an increment of 250. A comparison of structural and optical properties of CR-39 polymer before and after ion implantation was made. The increase in ion flux leads to the transformation of polymer into rather more disordered amorphous state leading to the broadening of XRD peaks. The crystallite size decreases (3.547 to 1.618 nm) and Urbach energy increases (0.232 to 0.291 eV) exponentially with the increase in ion flux (0 to 6.07 × 10 5 ions/cm 2 ). Indirect optical band gap is found to decrease (4.118 to 3.917 eV) linearly with the increase in ion flux (3.03×10 5 to 6.07×10 5 ions/cm 2 ).